Effect of alcoholic beverages as marinade ingredient for beef tapa - Forto, Cherry Amour C.
ABSTRACT The study investigated the bacteriostatic effect of some Philippine alcoholic drinks as applied to marinades for beef tapa. Lambanog, rice wine and bignay wine were tested for their bacteriostatic capabilities. The study first focused on selecting a recipe for beef tapa which was used as the basis for the formulation of the non-traditional marinades. The second phase of the study evaluated the bacteriostatic effect of the marinades. It first determined the important characteristics (e.g. pH and titratable acidity) of the wines and spirits which may have a contribution to their bacteriostatic ability aside from their ethanol content. The marinades were assessed for their bacteriostatic abilities by subjecting the tapa samples to aerobic plate count. Finally, the beef tapa formulation with the most effective bacteriostatic capability was compared to traditional beef tapa in terms of sensory acceptance. The recipe selected was a formulation from Ibarra (1989) which had the highest ranking from among three recipes and was described by randomly selected (n=50) panelists as having just the right amount of saltiness and peppery taste. Physicochemical evaluation of the three alcoholic beverages showed that rice wine had significantly higher pH and ethanol content. Although there were no significant (p>0.05) differences between the bacterial counts of treated samples and traditional beef tapa, the potential for the use of local wines as marinades is manifested by the (at least) 2 log difference in the microbial load. Rice wine marinated beef tapa was consequently chosen for phase 3 because of the bacteriostatic ability and the relative cost of the wine. Traditional beef tapa samples had significantly (p<0.05) more acceptable attributes except for color and overall acceptance compared to the rice wine marinated samples. The study presented the feasibility of rice wine as marinated ingredient which could possibly improve the safety and quality of traditionally prepared beef tapa.